Analisis Pelayanan Publik di Kelurahan Blabak Kota Kediri Menggunakan Dimensi Servqual - Muhamad Ansori (Universitas 17 Agustus 1945, 2025)
This study aims to analyse the quality of public services in Kelurahan Blabak using the SERVQUAL dimensions, so as to provide a comprehensive picture of the level of community satisfaction and provide input for improving service quality in the future. This research uses descriptive qualitative method to analyse the quality of public services in Blabak Village, Kediri City, based on the five dimensions of SERVQUAL. Data were collected through interviews, observations, and documentation, then analysed using interactive analysis with triangulation for data validity. The results showed that public services in Blabak Village, Kediri City, showed a fairly good quality based on the five dimensions of SERVQUAL. In terms of tangibles, facilities such as computers, printers, and internet networks are well available. However, limited space and seating are still an obstacle in providing comfort for the community. In reliability, administrative services, especially the processing of population documents, run quite reliably, especially with the presence of the SAKTI application which facilitates online processing and reduces queues. The responsiveness dimension is reflected in the readiness of officers to serve and respond to the needs of the community, although sometimes it is still constrained by technical problems such as internet networks. In the assurance dimension, people feel safe because the officers show a friendly and professional attitude, in accordance with the motto ‘Salam, Sapa, Senyum,’ which creates a warm and pleasant service atmosphere. Meanwhile, empathy can be seen from the officers' concern for the community, despite the limited number of personnel and diverse educational backgrounds, they still try to serve optimally. Thus, despite the challenges, public services in Blabak Village have run quite optimally. However, improvements are needed in terms of infrastructure and the number of officers so that services can be more comfortable, fast, and efficient.